PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN EREMERASA KABUPATEN BANTAENG - Hidayati, Andi (Indonesian Journal Of Economy Studies, 2023)
The purpose of this research are: 1) To determine the influence of leadership on employee performance at the Eremerasa Sub-District, Bantaeng Regency, 2) To determine the influence of organizational culture on employee performance at the Eremerasa Sub-District, Bantaeng Regency, 3) To determine the influence of work discipline on employee performance at the Eremerasa Sub-District Office, Bantaeng Regency, 4) To determine the simultaneous influence of leadership, organizational culture, and work discipline on employee performance at the Eremerasa Sub-District, Bantaeng Regency, 5) To identify which variable has a greater influence among leadership, organizational culture, and work discipline on employee performance at the Eremerasa Sub-District, Bantaeng Regency.The research method employed in this study is a survey method with a quantitative approach, focusing on hypothesis testing. The population consists of 40 individuals, and the sample is drawn using a census method, resulting in a sample size of 40 respondents. Data is collected through questionnaires and direct observation. The data analysis is carried out descriptively using quantitative methods with the SPSS program, utilizing multiple linear regression analysis.The research findings indicate that leadership, organizational culture, and work discipline collectively have an 84% influence on employee performance at the Eremerasa Sub-District, Bantaeng Regency, while the remaining 16% is explained by other variables not examined in this study. Leadership has the most dominant influence on employee performance at the Eremerasa Sub-District, Bantaeng Regency, with standardized Beta coefficient values of Leadership (X1), organizational culture (X2), work discipline (X3), and the dependent variable employee performance (Y) being 0.345, 0.283, and 0.317, respectively. The highest indicator value for the Leadership variable is attributed to organizational factors.